Femoral neck system versus dynamic hip screw for fixation of femoral neck fracture in the adult: a meta-analysis - Qi Long Jiang; Yong Cao; Xinwen Bai; Yu Deng; Yan Li (Journal of the Pakistan Medical Association)
Objective: To determine the efficacy of femoral neck system compared to dynamic hip screws in treating femoral neck fractures.